1997
DOI: 10.1021/ja970069f
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Electronic Energy Transfer in Ruthenium(II) Diimine Donor/Pyrene Acceptor Complexes Linked by a Single C−C Bond

Abstract: The photophysical behavior of [(bpy) 2 Ru(L)] 2+ complexes (L ) 4-(1′′-pyrenyl)-2,2′-bipyridine, bpy-pyr; 2-(1′-pyrenyl)-1,10-phenanthroline, phen-pyr; and 2-(2′-naphthyl)-1,10-phenanthroline, phen-nap) was investigated in solutions and frozen matrices. The conformation of the linked pyrene differs in the two complexes: The pyrene moiety is conformationally constrained to be nearly perpendicular to the phenanthroline in the phen-pyr complex while the pyrene in the bpy-pyr complex has much greater flexibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
214
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(232 citation statements)
references
References 44 publications
18
214
0
Order By: Relevance
“…[9][10][11] In particular, we have observed from NMR studies, taken with the compounds here reported and also with similar systems, containing anthracene (or benzene) as the emissive chromophore instead of naphthalene, that the first proton release always takes place with the central nitrogens. [8][9][10][11] On the other hand, the protonation sequence is mainly ruled by the existence of a minimum of repulsion between equally charged species. The obtained exponential dependence for the quenching rate constant, shown in Figure 2, is of general formula, k q ) k q (0) exp(-d), leading to a factor of 0.45 Å -1 , 1-7 suggesting that electron transfer would occur at longer distances than expected for an aliphatic system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In particular, we have observed from NMR studies, taken with the compounds here reported and also with similar systems, containing anthracene (or benzene) as the emissive chromophore instead of naphthalene, that the first proton release always takes place with the central nitrogens. [8][9][10][11] On the other hand, the protonation sequence is mainly ruled by the existence of a minimum of repulsion between equally charged species. The obtained exponential dependence for the quenching rate constant, shown in Figure 2, is of general formula, k q ) k q (0) exp(-d), leading to a factor of 0.45 Å -1 , 1-7 suggesting that electron transfer would occur at longer distances than expected for an aliphatic system.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] In previous work, carried out in systems containing a polyamine chain bearing a terminal aromatic fluorophore, we have shown that the most intense emission occurs for the fully protonated form and that proton abstraction from the polyaminic chain leads to a decrease in the emission intensity. [8][9][10][11] This quenching effect is due to the intramolecular electron transfer process involving the lone pair of a deprotonated amine and the excited fluorophore. Moreover, it was also observed that the degree of quenching shows a crucial dependence, not only with the chain length but also with the stage of protonation.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of facts, electron transfer/transport processes are not sensitive enough to this type of parameter, [17e, 18b, 18c, 19a] contrary to luminescence [52] under proper conditions mentioned above. [64] A possible application of such switching effects could be for an optical information storage at the molecular level based on the luminescence of *P. [65] Also, the derived possibility of a conformational tuning of nonlinear two-photon absorption processes [66] that could be use for molecule-based photonic materials should be investigated inasmuch the type of compounds studied are also known to exhibit NLO properties. [67,68] …”
Section: General Commentsmentioning
confidence: 99%
“…[5] In fact, several studies have described triplet energy transfer from a metal complex to an aryl hydrocarbon, [6±11] but in several cases the photosystems are unstable with respect to sensitized oxygenation of the polycycle. [6,7,9] Very recently, Schmehl and co-workers [12] studied the photophysical properties of ruthenium(ii) tris(diimine) complexes linked by a single bond to naphthalene or pyrene. It was concluded that the closely spaced terminals remained in weak electronic communication and that triplet states associated with these terminals were not in equilibrium at room temperature.…”
Section: Introductionmentioning
confidence: 99%